2013
DOI: 10.1007/s00464-013-3259-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic liver resection: 5-year experience at a single center

Abstract: Background Hepatocellular carcinoma (HCC) is a common cancer, especially in the Association of Southeast Asian Nations (ASEAN) region, where the prevalence of hepatitis virus infection is high. Liver resection is a potentially curative and popular therapy for HCC. Laparoscopic surgery using minimally invasive techniques potentially brings benefits to patients who need liver resection for HCC. This study aimed to evaluate the effectiveness, safety, and benefits of laparoscopic liver resection for HCC with long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
4
22
1
Order By: Relevance
“…Nonetheless, although we have demonstrated that open conversion results in poorer perioperative outcomes, it is imperative to remember that conversion per se should not be considered a failure or complication as patient safety and oncologic integrity is of utmost importance [10]. Conversion rates for LH have been reported to range from 0 to 55 % in the literature depending on the experience of the center and type of resections in the study [10,[20][21][22]. Some authors [15] have also proposed a policy of early conversion to reduce blood loss and operative time with the aim of improving patient safety.…”
Section: Discussionmentioning
confidence: 90%
“…Nonetheless, although we have demonstrated that open conversion results in poorer perioperative outcomes, it is imperative to remember that conversion per se should not be considered a failure or complication as patient safety and oncologic integrity is of utmost importance [10]. Conversion rates for LH have been reported to range from 0 to 55 % in the literature depending on the experience of the center and type of resections in the study [10,[20][21][22]. Some authors [15] have also proposed a policy of early conversion to reduce blood loss and operative time with the aim of improving patient safety.…”
Section: Discussionmentioning
confidence: 90%
“…LH may thus have advantages regarding tumor removal, while RFA may have advantage in relation to minimal invasiveness. Laparoscopic liver resection evolved from traditional liver resection, but is superior in several ways: It can be performed on a microscopic scale, offers a clean and clear surgical field, and allows for fine-featured anatomical resection [27]. It has thus been used extensively for more Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of chronic liver disease, many centres are reluctant to employ a laparoscopic resection owing to what were, initially, well‐founded technical concerns. However, there is now a growing body of literature to support the safety and adequacy of LLR in the setting of benign and metastatic disease . This study sought to examine the utility of LLR for HCC compared with OLR in a single, large volume, North American institution.…”
Section: Discussionmentioning
confidence: 99%